2019
DOI: 10.1386/cjcs_00005_1
|View full text |Cite
|
Sign up to set email alerts
|

Framing Catalonia: Evidence from Québec media

Abstract: This article assesses the media treatment of the Catalan referendum on independence (October 2017) in the Québec context. By conducting a quantitative and deductive content analysis of articles published in the four major Québec newspapers, we analyse how Québec newspapers frames the conflict regarding their historical editorial position about the Québec independence project. In addition, we examine how the comparison between Québec and Catalonia fit into the media coverage. Our results confirm the dominant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In particular, the street demonstrations that have accompanied the political process have been widely studied (e.g., Alonso-Muñoz, 2014; Capdevila & Moragas-Fernández, 2019; Castelló, 2015; Gili et al, 2018; Moragas-Fernández & Capdevila, 2017; Palà Navarro, 2018; Xambó et al, 2014) while the secession process has also attracted interest from researchers examining the use of social media, its coverage in the national media, the strategies of the political parties, and the role played by television and radio (Algaba & Bellido-Pérez, 2019; Ballesteros, 2015; Guerrero-Solé, 2017; Martínez & Álvarez-Peralta, 2016; Monferrer & Bellido, 2018; Palà Navarro, 2020; Perales-García et al, 2019; Pont-Sorribes et al, 2018; Sampedro et al, 2021; San Cornelio & Gómez, 2019; Xicoy-Comas et al, 2017, 2020). Finally, research into the international repercussions of the process has been the object of several studies, especially devoted to the treatment given to the Catalan conflict in the international press (e.g., Dubois & Villeneuve-Siconnelly, 2019; Høeberg, 2014; Perales-García & Pont-Sorribes, 2018; Pont-Sorribes et al, 2019).…”
Section: Academic Literature On the Catalan Secession Processmentioning
confidence: 99%
“…In particular, the street demonstrations that have accompanied the political process have been widely studied (e.g., Alonso-Muñoz, 2014; Capdevila & Moragas-Fernández, 2019; Castelló, 2015; Gili et al, 2018; Moragas-Fernández & Capdevila, 2017; Palà Navarro, 2018; Xambó et al, 2014) while the secession process has also attracted interest from researchers examining the use of social media, its coverage in the national media, the strategies of the political parties, and the role played by television and radio (Algaba & Bellido-Pérez, 2019; Ballesteros, 2015; Guerrero-Solé, 2017; Martínez & Álvarez-Peralta, 2016; Monferrer & Bellido, 2018; Palà Navarro, 2020; Perales-García et al, 2019; Pont-Sorribes et al, 2018; Sampedro et al, 2021; San Cornelio & Gómez, 2019; Xicoy-Comas et al, 2017, 2020). Finally, research into the international repercussions of the process has been the object of several studies, especially devoted to the treatment given to the Catalan conflict in the international press (e.g., Dubois & Villeneuve-Siconnelly, 2019; Høeberg, 2014; Perales-García & Pont-Sorribes, 2018; Pont-Sorribes et al, 2019).…”
Section: Academic Literature On the Catalan Secession Processmentioning
confidence: 99%
“…Dubois & Villeneuve-Siconnelly, 2019) and the discussions on Twitter concerning the conflict(Moragas-Fernández et al, 2019). In this respect, according toCarrasco et al (2018), the pro-independence movement showed a higher mobilization on social networks than the pro-unionists, which was explained in the previous section as being due to the grassroots nature of the mobilization of the Catalan citizens.Therefore, it can be said that polarization was a defining aspect of the social debate which took place on Twitter, the social network which awoke the highest level of interest among its users(Moragas-Fernández et al, 2019; Hernández-Santaolalla & Sola-Rocío Zamora-Medina and Leonarda García-Jiménez DOI: 10.25200/BJR.v18n1.2022.1421Morales, 2019;Carrasco et al, 2018;Pérez Curiel, 2020), possibly due to its conversational nature.…”
mentioning
confidence: 93%
“…The large number of samples which we have read in order to carry out our research (901 press articles and 3.822 Twitter posts) makes this a methodical and rigorous study of how the traditional media (in this case printed) and the social networks (specifically Twitter) interpreted the events that occurred between October 1st and October 8th, 2017. This research does not focus exclusively on either the press (Vellón, 2020;Pont-Sorribes et al, 2019;Dubois & Villeneuve-Siconnelly, 2019;Perales-García & Pont-Sorribes, 2017;Cartes-Barroso, 2018;Dorado & Sixto-García, 2021;Xicoy et al, 2017;Irala-Hortal, 2020) or on social networks (Anderson, 2019;San Cornelio & Gómez Cruz, 2019;Carrasco et al, 2018;Hernández-Santaolalla & Sola-Morales, 2019;Gil Ramírez, 2019) as other previous studies have done, but instead includes both, in their textual and visual dimensions, which allowed us to establish diverse comparatives of the regional/national/international axes and/or the press and Twitter, which enriches the exploration of the discursive and communicative complexity which characterized the events of October 1st. As can be seen, this comparative approximation has been less frequently employed in the field of communication research in Spain (Pérez Curiel, 2020).…”
mentioning
confidence: 99%